Effects of Ductile Fiber Size on the Fracture Toughness of Copper/Polyester Composites - Kaman, Mete Onur; Solmaz, Murat Yavuz; Turan, Kadir (Sage Publications Ltd, 2010)
The objective of this study is to examine the effect of fiber size on the fracture toughness of ductile fiber reinforced composite materials. For this purpose, pull-out tests of copper fiber embedded in polyester matrix have been conducted, as a result of which load-displacement graphics for different fiber diameters and embedded lengths have been obtained. Using the derived load-displacement graphics, debonding load of each specimen has been found, and sliding shear stress, bond shear stress, and pull-out work have been calculated. Then, fracture energy increments per unit cross-sectional area have been determined. In the numeric part of the study, pull-out test was modeled using finite element package program ANSYS (11.0). With the help of this model, load-displacement graphic obtained in the test has been repeated in numeric terms. Obtained results have been presented in the form of tables and graphs and interpreted. It has been observed that the fracture energy increment increases with increase in the diameter of the copper fiber.
Keywords: mechanical testing; finite element method; debonding; fracture toughness